Intrinsic judgment error in men’s championship world surf league: WSL 2021 - Tony Meireles Santos; Lucas Eduardo Rodrigues Santos; Ítalo Vinicius; Cayque Brietzke; Lucas Camilo Pereira; Paulo Henrique Melo; Thaiene Camila Beltrão Moura; Taddeo De Negri; Hassan Mohamed Elsangedy; Flávio Oliveira Pires (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Surfers’ performances are subjectively ranked by 5 judges. Low reliability and validity in judgment may lead to preventable errors and unfair scores.